Sodium ion battery and preparation method and application thereof

A two-stage sintering process with LALZO coating on sodium-ion battery electrodes stabilizes the material against air and electrolyte reactions, improving cycle and rate performance by ensuring uniform coating and ion mobility.

CN119208562APending Publication Date: 2024-12-27TONGREN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411327224.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Layered oxide materials for sodium-ion batteries suffer from air instability, leading to capacity decay, sodium dissolution, and electrolyte corrosion due to reactions with air and water, which are not effectively mitigated by traditional nanoparticle coating methods.

Method used

A two-stage sintering process is employed to coat the positive electrode layered oxide material with LALZO (aluminum-doped lithium lanthanum zirconium oxygen solid electrolyte), using alcohol to clean the surface and ensure uniform coating, maintaining interlayer spacing and improving air stability and ion mobility.

Benefits of technology

The method enhances the cycle stability and rate performance of sodium-ion batteries by preventing corrosion and ensuring a uniform, high ionic conductivity coating, addressing the issues of capacity decay and electrolyte reactivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208562A_ABST
    Figure CN119208562A_ABST
Patent Text Reader

Abstract

The invention provides a sodium ion battery and a preparation method and application thereof, and the preparation method of the sodium ion battery comprises the following steps: mixing a positive electrode layered oxide material with LALZO, adding alcohol, stirring, and sintering at high temperature to obtain a LALZO-coated sodium ion battery positive electrode layered oxide material; the step of high-temperature sintering comprises the steps of sintering at the temperature of 200-400 DEG C for 2-6 hours, and then sintering at the temperature of 550-850 DEG C for 1-8 hours. According to the preparation method disclosed by the invention, the surface of the material is coated with LALZO, so that side reaction with oxygen and water and electrolyte corrosion caused by exposure in air can be prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sodium ion battery preparation, and in particular to a sodium ion battery and a preparation method and application thereof. Background Art

[0002] Due to the scarcity of lithium resources and the rising prices of raw lithium compounds as electric vehicles are promoted, and the low safety of lithium-ion secondary batteries, the development of secondary batteries with new ion systems has become a research focus in recent years. Sodium and lithium are in the same main group, with similar chemical properties, and sodium is abundant and inexpensive, which makes sodium-ion batteries a feasible alternative to lithium-ion batteries in the energy storage field.

[0003] Layered oxide materials for the positive electrode of sodium-ion batteries have advantages such as structural stability and can provide the largest-dimensional transmission channel for sodium ions, but they are unstable in air storage, manifested as capacity decay, increased excess potential and the formation of alkaline substances. Higher iron content produces 03-type materials that are determined to react more strongly with air, resulting in sodium dissolution and carbonate formation on the surface. During air degradation, sodium carbonate is produced on the surface of the particles, which is the result of the reaction between the lattice Na+ and carbon dioxide in the air. At the same time, water molecules play an important role in accelerating the dissolution of Na+ from the lattice through Na / H+ exchange, leading to the formation of a hydrated phase or structural transition. Therefore, finding innovative strategies to optimize the manufacturing process and minimize the cost of air protection is crucial to improving the commercial viability and widespread adoption of sodium-ion batteries.

[0004] In view of the above-mentioned problems existing in the positive electrode layered oxide materials, the existing improvement means are mainly surface coating. By coating the layered oxide surface, the positive electrode material can be separated from the air, the side reactions can be reduced, the material can be protected from reacting with the electrolyte, and the generation of alkali can be inhibited, thereby optimizing the material's cycle performance, safety performance and rate performance. Specifically, the traditional approach is generally to mix the electrode material with nanoparticles in a solid phase, but this method cannot effectively control the thickness of the nanoparticles coated on the surface of the positive electrode material particles, and the alkaline substances that have been generated still exist on the surface of the material, causing the sodium battery positive electrode material to suffer from corrosion, performance degradation and cracks in the positive electrode material particles during the cycle.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The first object of the present invention is to provide a method for preparing a sodium ion battery, which can prevent the battery from being exposed to the air and causing side reactions with oxygen and water and electrolyte corrosion by coating the surface of the battery positive electrode layered oxide material with LALZO solid electrolyte. The segmented setting of the sintering temperature is conducive to the uniform coating of LALZO on the surface of the material, maintaining the original interlayer spacing of the material, and improving the performance, thereby achieving the best coating effect. In addition, the positive electrode layered oxide material of the sodium ion battery can react with water, resulting in structural collapse and performance degradation, so the surface sodium residue can be effectively removed by using alcohols.

[0007] The second object of the present invention is to provide a sodium ion battery prepared by the above-mentioned preparation method, wherein the sodium ion battery is a sodium ion battery positive electrode layered oxide material coated with LALZO (aluminum-doped lithium lanthanum zirconium oxygen solid electrolyte), and the material has good ion mobility, good air stability, and is not easily corroded by the electrolyte.

[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0009] The present invention provides a method for preparing a sodium ion battery, comprising the following steps:

[0010] The positive electrode layered oxide material and LALZO are mixed, alcohol is added, stirred, and sintered at high temperature to obtain a positive electrode layered oxide material for a sodium ion battery coated with LALZO;

[0011] The high temperature sintering step includes sintering at a temperature of 200° C.-400° C. for 2 h-6 h, and then sintering at a temperature of 550° C.-850° C. for 1 h-8 h.

[0012] The present invention mixes the positive electrode layered oxide material with LALZO, then adds the solution for stirring, and then performs segmented high-temperature sintering, which can remove the positive electrode layered oxide (Na X TMO2) The alkali remaining on the surface of the material can also be coated on the surface of the material, achieving the technical effects of good ion mobility, good air stability, and not being easily corroded by the electrolyte in the sodium battery positive electrode material.

[0013] The modification method provided by the present invention not only has few operating steps, simple process, high success rate, and is suitable for large-scale promotion and production, but also solves the technical problems of poor capacity, poor air stability, and low rate of sodium battery positive electrode materials in the prior art, and achieves the technical effects of good ion mobility, good air stability, and not being easily corroded by electrolyte in the positive electrode material.

[0014] After the positive electrode layered oxide material is mixed with LALZO, a solution is subsequently added. The reason for adding alcohol is that the presence of the alcohol solution can clean the alkali remaining on the surface of the material, and at the same time, LALZO can be more evenly mixed with the material, which has the effect of improving the mixing effect.

[0015] Preferably, as a further feasible solution, the alcohol includes at least one of methanol, ethanol, propanol, isopropanol, butanol, ethylene glycol, isobutanol, sec-butanol, tert-butanol, n-pentanol, sec-pentanol, n-octanol, sec-octanol and n-hexanol. Ethanol is the best choice among the above alcohols, because ethanol is not only easy to obtain, but also relatively safe and has excellent removal effect. During the stirring process, LALZO is mixed more evenly with the material, and then the alcohol is evaporated by high-temperature sintering, and LALZO will form a coating on the surface of the material.

[0016] Preferably, as a further feasible solution, the high temperature sintering step comprises: sintering at a temperature of 250° C.-350° C. for 3 h-4 h, and then sintering at a temperature of 600° C.-700° C. for 2 h-6 h.

[0017] The first step of high temperature sintering has a sintering temperature of 200°C, 250°C, 300°C, 350°C, and 400°C. The time is 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, and 6h. The second step of sintering has a sintering temperature of 550°C, 600°C, 650°C, 700°C, and 850°C. The time is 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, and 8h.

[0018] The reason why the present invention adopts staged calcination to form a LALZO coating on the surface of the material is that the LALZO coating layer generated by the two-stage temperature calcination is more uniform and has the characteristics of high stability and high ionic conductivity, thereby solving the technical problems of poor capacity, poor air stability and low rate of sodium positive electrode materials in the prior art; in addition, the coating method provided by the present invention has fewer operating steps, simple process, high success rate, and is suitable for large-scale promotion and production.

[0019] Therefore, it is found in the specific practice that the two-stage roasting method is adopted, and each roasting stage is carried out according to the operating temperature and operating time of the present invention, which can ensure that the prepared material has more excellent performance and improve the stability of the material itself, so it is best to operate according to the scheme of the present invention.

[0020] Preferably, as a further feasible solution, the amount of LALZO used is 0.1%-3% by weight of the positive electrode layered oxide material, preferably 0.5%-2.5%, and more preferably 1-2%.

[0021] For example, you can also choose 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, and 2.9%.

[0022] Preferably, as a further feasible solution, grinding is performed after mixing, and the grinding time is 20-60 min.

[0023] Preferably, as a further feasible solution, alcohol is added after grinding and the stirring time is 10-40 minutes.

[0024] Preferably, as a further feasible solution, the high temperature sintering is followed by cooling, and the cooling rate is 0.5°C / min-1°C / min, for example, 0.5°C / min, 0.6°C / min, 0.7°C / min, 0.8°C / min, 0.9°C / min.

[0025] The present invention also provides a sodium ion battery prepared by the above preparation method.

[0026] The sodium ion battery of the present invention has good cycle stability, good rate performance and excellent working performance.

[0027] The sodium ion battery further comprises an electrolyte and a separator in addition to the positive electrode sheet of the positive electrode material of the present invention;

[0028] Available electrolytes are generally obtained by dissolving sodium salts in organic solvents;

[0029] Wherein, the available sodium salts include: at least one of NaPF6 and NaClO4;

[0030] The organic solvent used is mainly an anhydrous solvent, including at least one of carbonates (ethylene carbonate, propylene carbonate and diethyl carbonate, etc.), 1,2-dimethoxyethane, tetrahydrofuran and 2-methyltetrahydrofuran;

[0031] Useful separators include at least one of a single-layer polypropylene film, a polyethylene film, a polyethylene / polypropylene / polyethylene composite film, a cellulose nonwoven separator, and glass fiber.

[0032] In conclusion, the sodium ion battery prepared by the preparation method of the present invention has good application in device driving. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] By reading the detailed description of the preferred embodiment below, various other advantages and benefits will become clear to those of ordinary skill in the art. The accompanying drawings are only used for the purpose of illustrating the preferred embodiment and are not considered to be limitations of the present invention. In addition, the same reference symbols are used to represent the same components throughout the accompanying drawings.

[0034] Figure 1 The XRD spectrum of the positive electrode layered oxide material provided in Example 1 of the present invention;

[0035] Figure 2 The SEM spectrum of the positive electrode layered oxide material provided in Example 1 of the present invention;

[0036] Figure 3 XRD spectrum of the positive electrode layered oxide material provided in Comparative Example 1;

[0037] Figure 4 The SEM spectrum of the positive electrode layered oxide material provided in Comparative Example 1;

[0038] Figure 5 XRD spectrum of the positive electrode layered oxide material provided in Comparative Example 2;

[0039] Figure 6 The SEM spectrum of the positive electrode layered oxide material provided for Comparative Example 2;

[0040] Figure 7 A comparison chart of the cycle performance of the positive electrode layered oxide material obtained in Example 1 of the present invention and Comparative Examples 1-3;

[0041] Figure 8 The figure is a comparison chart of the rate performance of the positive electrode layered oxide material obtained in Example 1 of the present invention and Comparative Example 1 respectively. DETAILED DESCRIPTION

[0042] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0043] Example 1

[0044] A method for coating LALZO (aluminum-doped lithium lanthanum zirconium oxygen solid electrolyte) with a sodium ion battery positive electrode layered oxide material comprises the following steps:

[0045] (1) Sodium carbonate, nickel oxide, iron oxide and manganese tetraoxide are solid-phase sintered to obtain a positive electrode layered oxide material (NaMn 0.33 Fe 0.33 Ni 0.33 O2);

[0046] (2) Grinding the positive electrode layered oxide material and LALZO for 40 min, adding ethanol and stirring for 30 min, and then filtering;

[0047] Wherein, the amount of LALZO is 2wt% of the positive electrode layered oxide material;

[0048] (3) The positive electrode layered oxide material after grinding, stirring and filtering was first sintered at 300°C for 4 hours and then sintered at 700°C for 3 hours. The cooling temperature and time were 1°C / min to obtain a LALZO-coated positive electrode layered oxide material. The XRD spectrum is shown in Figure 1 , its SEM spectrum is shown in Figure 2 .

[0049] Example 2

[0050] A method for coating LALZO (aluminum-doped lithium lanthanum zirconium oxygen solid electrolyte) with a sodium ion battery positive electrode layered oxide material comprises the following steps:

[0051] (1) Sodium carbonate, nickel oxide, iron oxide and manganese tetraoxide are solid-phase sintered to obtain a positive electrode layered oxide material (NaMn 0.33 Fe 0.33 Ni 0.33 O2);

[0052] (2) Grinding the positive electrode layered oxide material and LALZO for 40 min, adding ethanol and stirring for 30 min, and then filtering;

[0053] Wherein, the amount of LALZO is 2wt% of the positive electrode layered oxide material;

[0054] (3) The positive electrode layered oxide material after grinding, stirring and filtering was first sintered at 350° C. for 4 h, and then sintered at 850° C. for 1 h, with the cooling temperature and time being 1° C. / min, to obtain a LALZO-coated positive electrode layered oxide material.

[0055] Example 3

[0056] A method for coating LALZO (aluminum-doped lithium lanthanum zirconium oxygen solid electrolyte) with a sodium ion battery positive electrode layered oxide material comprises the following steps:

[0057] (1) Sodium carbonate, nickel oxide, iron oxide and manganese tetraoxide are solid-phase sintered to obtain a positive electrode layered oxide material (NaMn 0.33 Fe 0.33 Ni 0.33 O2);

[0058] (2) Grinding the positive electrode layered oxide material and LALZO for 40 min, adding ethanol and stirring for 30 min, and then filtering;

[0059] Wherein, the amount of LALZO is 2wt% of the positive electrode layered oxide material;

[0060] (3) The positive electrode layered oxide material after grinding, stirring and filtering was first sintered at 300° C. for 5 h, and then sintered at 550° C. for 1 h, with the cooling temperature and time being 1° C. / min, to obtain a LALZO-coated positive electrode layered oxide material.

[0061] Example 4

[0062] A method for coating LALZO (aluminum-doped lithium lanthanum zirconium oxygen solid electrolyte) with a sodium ion battery positive electrode layered oxide material comprises the following steps:

[0063] (1) Sodium carbonate, nickel oxide, iron oxide and manganese tetraoxide are solid-phase sintered to obtain a positive electrode layered oxide material (NaMn 0.33 Fe 0.33 Ni 0.33 O2);

[0064] (2) Grinding the positive electrode layered oxide material and LALZO for 40 min, adding ethanol and stirring for 30 min, and then filtering;

[0065] Wherein, the amount of LALZO is 1wt% of the positive electrode layered oxide material;

[0066] (3) The positive electrode layered oxide material after grinding, stirring and filtering was first sintered at 300° C. for 5 h, and then sintered at 700° C. for 5 h, with the cooling temperature and time being 0.5° C. / min, to obtain a LALZO-coated positive electrode layered oxide material.

[0067] Example 5

[0068] A method for coating LALZO (aluminum-doped lithium lanthanum zirconium oxygen solid electrolyte) with a sodium ion battery positive electrode layered oxide material comprises the following steps:

[0069] (1) Sodium carbonate, nickel oxide, iron oxide and manganese tetraoxide are solid-phase sintered to obtain a positive electrode layered oxide material (NaMn 0.33 Fe 0.33 Ni 0.33O2);

[0070] (2) Grinding the positive electrode layered oxide material and LALZO for 40 min, adding ethanol and stirring for 30 min, and then filtering;

[0071] Wherein, the amount of LALZO is 1wt% of the positive electrode layered oxide material;

[0072] (3) The positive electrode layered oxide material after grinding, stirring and filtering was first sintered at 250° C. for 3 h, and then sintered at 700° C. for 3 h, with the cooling temperature and time being 1° C. / min, to obtain a LALZO-coated positive electrode layered oxide material.

[0073] Comparative Example 1

[0074] A sodium ion battery positive electrode layered oxide material is prepared by the following method:

[0075] Sodium carbonate, nickel oxide, iron oxide and manganese tetraoxide are solid-phase sintered to obtain a positive electrode layered oxide material (NaMn 0.33 Fe 0.33 Ni 0.33 O2). Its XRD spectrum is shown in Figure 3 , its SEM spectrum is shown in Figure 4 .

[0076] Comparative Example 2

[0077] A method for coating LALZO (aluminum-doped lithium lanthanum zirconium oxygen solid electrolyte) with a sodium ion battery positive electrode layered oxide material comprises the following steps:

[0078] (1) Sodium carbonate, nickel oxide, iron oxide and manganese tetraoxide are solid-phase sintered to obtain a positive electrode layered oxide material (NaMn 0.33 Fe 0.33 Ni 0.33 O2);

[0079] (2) Grinding the positive electrode layered oxide material and LALZO for 40 min, adding ethanol and stirring for 30 min, and then filtering;

[0080] Wherein, the amount of LALZO is 2wt% of the positive electrode layered oxide material;

[0081] (3) The positive electrode layered oxide material after grinding, stirring and filtering was sintered at 300°C for 4 hours, and the cooling temperature and time were 1°C / min to obtain a positive electrode layered oxide material coated with LALZO. Its XRD spectrum is shown in Figure 5 , its SEM spectrum is shown in Figure 6 .

[0082] Comparative Example 3

[0083] A method for coating LALZO (aluminum-doped lithium lanthanum zirconium oxygen solid electrolyte) with a sodium ion battery positive electrode layered oxide material comprises the following steps:

[0084] (1) Sodium carbonate, nickel oxide, iron oxide and manganese tetraoxide are solid-phase sintered to obtain a positive electrode layered oxide material (NaMn 0.33 Fe 0.33 Ni 0.33 O2);

[0085] (2) Grinding the positive electrode layered oxide material and LALZO for 40 min, adding ethanol and stirring for 30 min, and then filtering;

[0086] Wherein, the amount of LALZO is 2wt% of the positive electrode layered oxide material;

[0087] (3) The positive electrode layered oxide material after grinding, stirring and filtering was sintered at 700° C. for 3 h, and the cooling temperature and time were 1° C. / min to obtain a LALZO-coated positive electrode layered oxide material.

[0088] Experimental Example 1

[0089] The materials prepared in Example 1 and Comparative Examples 1-3 were used as positive electrodes, 1 mol / L NaClO4 in EC:DEC=1:1 Vol% with 5% FEC was used as electrolyte, and glass fiber was used as separator to assemble into 2025 button cells;

[0090] The battery performance was tested at 120 mA / g. The cycle results are shown in Figure 7 , the cycle comparison is shown in Table 1.

[0091] The materials prepared in Example 1 and Comparative Example 1 were used as positive electrodes, 1 mol / L NaClO4 in EC:DEC=1:1 Vol% with 5% FEC was used as electrolyte, and glass fiber was used as separator to assemble into 2025 button cells;

[0092] The battery performance was tested at 120 mA / g. The rate results are shown in Figure 8 The ratio comparison is shown in Table 2.

[0093] Table 1 Cycle comparison table

[0094]

[0095] Table 2 Ratio comparison table

[0096]

[0097] Depend on Figure 5It can be seen that the XRD peak of Example 1 is more biased to the left than that of Comparative Example 2, indicating that the interlayer spacing of the material of Example 1 sintered twice is larger and the capacity is higher; Figure 2 and Figure 6 Comparison shows that the coating of Example 1 is more uniform than that of Comparative Example 2.

[0098] Depend on Figure 7 It can be seen that the capacity at 1C is 107.39 mAh / g (compared to 81.88 mAh / g in Comparative Example 1, 82.6 mAh / g in Comparative Example 2, and 87.9 mAh / g in Comparative Example 3); after 400 cycles, the capacity is still 75.43 mAh / g (compared to 39.27 mAh / g in Comparative Example 1, 46.62 mAh / g in Comparative Example 2, and 53.2 mAh / g in Comparative Example 3), indicating that it has very good cycle stability.

[0099] Depend on Figure 8 It can be seen that the capacity of the battery can reach 125.49 mAh / g at 0.1C, and the capacity is 57.75 mAh / g at 6C (compared to 34.1 mAh / g in Comparative Example 1), indicating that it has very good rate performance.

[0100] In summary, the present invention soaks the positive electrode layered oxide with LALZO, washes the residual alkali on the surface of the material with a solution, and then uses segmented high temperature to generate a uniform LALZO coating to obtain a positive electrode layered oxide material uniformly coated with LALZO; the present invention not only solves the problem of residual alkali on the surface of the positive electrode layered oxide material, but also coats a uniform high ionic conductivity LALZO protective film on the surface of the material, thereby maintaining the cycle performance of the layered material, improving the rate performance and specific capacity, so as to meet the actual use requirements of sodium ion batteries.

[0101] Although the present invention has been illustrated and described with specific embodiments, it will be appreciated that many other changes and modifications may be made without departing from the spirit and scope of the present invention. Therefore, it is intended to include all such changes and modifications within the scope of the present invention in the appended claims.

Claims

1. A method for preparing a sodium ion battery, characterized in that: The steps include: The positive electrode layered oxide material and LALZO are mixed, alcohol is added, stirred, and sintered at high temperature to obtain a positive electrode layered oxide material for a sodium ion battery coated with LALZO; The high temperature sintering step includes sintering at a temperature of 200° C.-400° C. for 2 h-6 h, and then sintering at a temperature of 550° C.-850° C. for 1 h-8 h.

2. The preparation method according to claim 1, characterized in that: The alcohol includes at least one of methanol, ethanol, propanol, isopropanol, butanol, ethylene glycol, isobutanol, sec-butanol, tert-butanol, n-pentanol, sec-pentanol, n-octanol, sec-octanol and n-hexanol.

3. The preparation method according to claim 1, characterized in that: The high temperature sintering step includes: sintering at a temperature of 250° C.-350° C. for 3 h-4 h, and then sintering at a temperature of 600° C.-700° C. for 2 h-6 h.

4. The preparation method according to claim 1, characterized in that: The amount of LALZO used is 0.1%-3% by weight of the positive electrode layered oxide material, preferably 0.5%-2.5%, and more preferably 1-2%.

5. The preparation method according to claim 1, characterized in that: After mixing, grinding is performed, and the grinding time is 20-60 minutes.

6. The preparation method according to claim 1, characterized in that: After grinding, add alcohol and stir for 10-40 minutes.

7. The preparation method according to claim 1, characterized in that: After high temperature sintering, the temperature is cooled at a rate of 0.5°C / min-1°C / min.

8. A sodium ion battery prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the sodium ion battery prepared by the preparation method according to any one of claims 1 to 7 and the sodium ion battery according to claim 8 in device driving.